PENERAPAN METODE ANALITYCAL HIERARCHY PROCESS DALAM PEMILIHAN SUPPLIER DENGAN PENDEKATAN SISTEM BERORIENTASI OBJEK - Aman, Mustar (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2022)
The current development of Information Technology, of course, has a major impact on very significant changes in various fields. Until now the supplier selection system at PT. Wika Realty, is not yet web-based because of problems with the system used for supplier data collection, which still uses conventional methods, and in determining the best supplier, you have to look at supplier data one by one, the assessment is still subjective, and there is no system that can determine the ranking of the value of the supplier determination analysis starting from the largest value to the smallest at PT. Wika Realty Jakarta. The purpose of this research is as an alternative to assist leaders in determining the appropriate supplier selection decisions, in selecting suppliers using alternative A, alternative B and alternative C. The method used is the Analytical Hierarchy Process method for the supplier selection process to make it more objective. The Analytical Hierarchy Process method is a process of comparing criteria into alternatives, the greater the value generated, the more important it is for the supplier to be selected, and in the analysis and design of the system, the system design method is object oriented programming using the Unified Modeling Language. Data collection by way of observation, interviews and literature study. The results of the research are in the form of software, namely a web-based decision support system for selecting the best supplier, which can present information on the best supplier data that fits the criteria quickly and precisely and supports digital concepts.